Micro accounting in the public sector: a study on the need for cost information on output produced for management purposes among federal government departments / Suria Su'ut - Su'ut, Suria (1986)
Today, governmental accounting is not traditionally confined to fund and budgetary accounting only. It has developed deeper into the accounting discipline known as micro accounting, in providing detailed information for analysis to the management. The term micro accounting in government signifies a better understanding of the management accounting discipline which is a combination ofproduct costing and management. The cost information provided could be used to indicate the cost performance by analysing the cost trend and variances, which is useful for the planning and optimum utilisation ofresources, budget control and activity management. This technique to management approach was derived from the theory of activity based costing designed by Cooper & Kaplan (1988). Thus, governmental micro accounting creates an information technology in providing accurate costing ofproduct or output produced byfederal depart- ments for strategic management purposes.